2012
DOI: 10.1111/j.2044-8287.2012.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress mediates the relationship between emotional loneliness and sleep quality over time in older adults

Abstract: We conclude that the impact of emotional loneliness on sleep quality in older adults is partly because of the stress experienced as a result of feeling lonely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 44 publications
5
76
1
2
Order By: Relevance
“…23 In our study, the poor sleep quality reported by the elderly was a determinant of loneliness. In their longitudinal observational study conducted with the elderly, McHugh and Lawlor 24 stated that loneliness increased perceived stress levels and thus reduced sleep quality. Kurina et al 23 stated that loneliness adversely affected individuals' perceptions of a safe social environment and thus deteriorated their sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…23 In our study, the poor sleep quality reported by the elderly was a determinant of loneliness. In their longitudinal observational study conducted with the elderly, McHugh and Lawlor 24 stated that loneliness increased perceived stress levels and thus reduced sleep quality. Kurina et al 23 stated that loneliness adversely affected individuals' perceptions of a safe social environment and thus deteriorated their sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…However, subjective social isolation was a stronger predictor of sleep disturbance, and in fact when both measures were simultaneously included in the same multivariable regression model, only subjective social isolation remained a significant predictor [17] .…”
Section: Social Isolation and Sleep Disturbancementioning
confidence: 99%
“…(119) Good relationship with friends and family is negatively correlated with poor sleep quality (P < 0.001) McHugh et al [17] Sleep disturbance Irish DJGLS, PSQI Emotional loneliness (subjective social isolation) rather than social loneliness (objective social isolation) is a stronger predictor of poor sleep quality (P < 0.001) Emotional loneliness increases stress (P < 0.001) Stress affects sleep quality (P < 0.0001) Gerst-Emerson et al [19] Depressive symptoms Aylaz et al [20] Depressive symptoms…”
Section: Social Isolation and Fatiguementioning
confidence: 99%
See 1 more Smart Citation
“…Studije posvećene relaciji između socijalne umreženosti i zdravstvenog statusa starih ukazale su na značajnu povezanost između usamljenosti i inflamatornog statusa i nesanice (Cacioppo, Hawkley, Norman, & Berntson, 2011), kardiovaskularnih bolesti (Hawkley, Thisted, Masi, & Cacioppo, 2010), osiromašene motorike (Buchman et al, 2009), ali i nepridržavanja lekarskih uputa tokom medicinske terapije (Segrin & Domschke, 2011). Jedan broj studija ukazuje da se ova veza između usamljenosti i zdravlja može objasniti činjenicom da usamljeni ljudi generalno manje vode računa o zdravstvenom ponašanju i slabije spavaju (Cacioppo et al, 2002) kao i da doživljavaju više stresa (McHugh & Lawlor, 2013) i osećaju pad životnog elana (Eng, Rimm, Fitzmaurice, & Kawachi, 2002).…”
unclassified